2013
DOI: 10.1080/17533015.2013.822397
|View full text |Cite
|
Sign up to set email alerts
|

Arts practice and disconnected youth in Australia: Impact and domains of change

Abstract: Background: This paper describes research conducted with Big hART, Australia's most awarded participatory arts company. It considers three projects, LUCKY, GOLD and NGAPARTJI NGAPARTJI across separate sites in Tasmania, Western NSW and Northern Territory, respectively, in order to understand project impact from the perspective of project participants, Arts workers, community members and funders. Methods: Semi-structured interviews were conducted with 29 respondents. The data were coded thematically and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In the elderly, arts engagement reduces depressed mood, enhances self-worth and promotes positive aging [ 27 , 28 ]. Arts programs for young people have been linked with improved motivation, self-image, hope for the future and self-esteem [ 29 ]. Where population-based studies have been conducted, arts engagement has been associated with perceptions of happiness and stress reduction [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, arts engagement reduces depressed mood, enhances self-worth and promotes positive aging [ 27 , 28 ]. Arts programs for young people have been linked with improved motivation, self-image, hope for the future and self-esteem [ 29 ]. Where population-based studies have been conducted, arts engagement has been associated with perceptions of happiness and stress reduction [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes associated with arts engagement are interconnected, iterative, relational and temporally bound 40. As postulated by Iyengar et al ,5 arts engagement was found to have a number of outcomes of individual and public consequence.…”
Section: Discussionmentioning
confidence: 95%
“…This is not to say that the framework is only relevant to the general population. Many of the outcomes included in the framework are also found in the arts programme literature 40 41. Therefore, although members of the general population were interviewed we believe that the framework equally applies to demographic subgroups and should also be useful when evaluating the outcomes of arts programmes, but that the effect of arts engagement on specific mental health, social, physical, economic, knowledge, arts-specific and identity outcomes may vary (ie, be larger or smaller) for specific groups due to effect modification, a list for which is provided in the framework.…”
Section: Discussionmentioning
confidence: 99%
“…In rural Australia, the arts are an important outlet for relaxation, self‐reflection and enjoyment 15,16 . Arts programs for disconnected youth and for people experiencing mental ill health have been linked with improved confidence, self‐esteem and hope for the future 17 . In the elderly, arts engagement reduces depressed mood and promotes positive ageing 18,19 .…”
Section: What Is Arts and Health?mentioning
confidence: 99%
“…The arts enhance social health by enabling both bridging and bonding social capital, 24 reducing feelings of isolation and increasing social support 5,15 . Participation in community arts projects increases perceptions of belonging and the development of civically valuable behaviours such as communication, tolerance, trust and respect 16,17,24–26 . As outlined in the Framework, arts events contribute to public health by providing opportunities for people to interact with others, form friendships and share in positive shared experiences 5,7 …”
Section: What Is Arts and Health?mentioning
confidence: 99%